A Comparative Study of the Impact of Social Media Advertisements on Working Women and Homemakers in Jaipur - Prajapat, Sunita (Mathematical Statistician and Engineering Applications, 2022)
The evolution of social media has transformed advertising strategies, providing businesses with innovative tools to target distinct audience segments effectively. This study investigates the impact of social media advertisements on working women and homemakers, examining their consumption patterns, engagement levels, and overall response to marketing strategies on platforms such as Facebook, Instagram, Twitter, and Pinterest. With social media use reaching approximately 4.9 billion people globally in 2023, advertisers have a unique opportunity to target specific demographics with personalized content. Online advertisements have significantly impacted the purchasing habits of the general public due to the increasing internet use. The online retail sector in India is transitioning, as many brands are shifting away from traditional brick-and-mortar stores. Various parameters of online advertising influence consumer behavior. As the online retail market in India continues to expand, new brands and shopping websites are emerging daily. Women consumers play a crucial role in this growth, as their buying behavior significantly influences the online shopping landscape across different platforms and applications. Social media advertising is rapidly evolving, with platforms like Instagram, Facebook, YouTube, and shopping apps such as Nykaa, Meesho, Amazon, and Myntra offering numerous shopping opportunities for women, featuring a wide range of national and international cosmetic brands. This research focuses on the influence of advertisements on homemakers, who have shifted from traditional media to social media. This also explores how working women use the knowledge gained through online advertisements. The study utilizes a quantitative research questionnaire survey method, gathering data from 100 women (50 working women and 50 homemakers) in Jaipur City to understand their behavior toward social media advertisements. The present research aims to explore a comparative study of the impact of online advertisements on working women and homemakers in Jaipur.